Enhancement For Image Capture Under Non–Homogenous Lightness Using Retinex Techniques - Al–Zuk, Ali A; Salman, Salema S; Sabah, Ban (Al-Nahrain Journal of Science, 2013)
In the present work retinex algorithm have been applied to enhance the capture image under nonhomogenous lighting, such enhancement algorithm can effectively enhance the image contrast, compared with enhanceme nt histogram equalization algorithm. The results show that the image after enhancement has the best contrast than the image before enhancement. Study results showed that lighting intensity distribution of imaging system source represents a linear relation with voltage. The diagram was approximated to a nearest straight line function. There inverse proportion between lighting intensity of imaging system source at the right side and lighting intensity of imaging system source at the left side of line cut from the width and height of test image , in the present study statistical characteristics of captured images were calculated with different lighting intensities before and after enhancement technique